Rediscovering and Reshaping the Notion of "Neighbor" - Engbwang SJ, Bernard (Lumen et Vita, 2015)
In the realm of Christian faith, the notion of “neighbor” represents a “gate for salvation.” In this work, my aim is to shed light on the necessity of rediscovering and reshaping what is meant by “neighbor” in the context of current worldwide challenges. In fact, it is a truism to say that our world is crossing one of the most critical periods of its evolution: Global warming, migrations crisis, terrorism, etc, all contribute to a complex situation. In the specific context of United States, there are racial and gender issues, gun violence, and other unique issues to take into account. All those critical situations reflect what we may call “crisis of neighborhood.” I propose in this paper, based on the Book of Genesis, a specific definition of neighbor: a helper desired by God to fulfill human person’s existential anxiety. In fact, in Gn 2:18, the declaration by God that it is good for the man not to be alone points to the necessity of having a neighbor. Here is the origin of neighborhood. Besides, it seems worthwhile to underline here the fact that the woman was not the first helper to be created. By way of reshaping, I aim to extend the notion of neighbor beyond a human person. In the NT, the notion is covered by the religious and social accent. The fact that Jesus extended its meaning beyond the community of Covenant to fit his message of love may pave our way even to the extent of a cosmic level, to deal with ecological issues. In that sense, plants and animals might be integrated in that notion.